Parenteral nutrition is not a fluid!. Issue 5 (13th April 2016) - Paltrinieri, A L; Cheng, I; Chitrit, M; Turnock, K
Abstract : Knowledge of the basic principles of parenteral nutrition is essential for any clinician working in paediatric and neonatal intensive care units. This article aims to give a brief review of the up-to-date recommendations for the paediatric population together with practical tips and considerations about current challenges and issues we believe are still open for debate, particularly with regard to neonates.